Deteksi Dini Gangguan Kejiwaan dan Peningkatan Kesehatan Mental Remaja melalui Fun Games: Early Detection of Mental Disorders and Enhancement of Adolescent Mental Health through Fun Games - Sapto Wibowo; Anung Priambodo; Junaidi Budi Prihanto; Nanang Indriarsa; Vega Candra Dinata; Kolektus Oky Ristanto (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
Early detection of mental disorders is crucial for preventing serious impacts on adolescent mental health. Fun games are used as an engaging and acceptable solution for adolescents to identify behavioral and emotional changes, raise mental health awareness, facilitate open dialogues, and reduce the stigma associated with mental disorders. This study aims to train PJOK teachers in Banyuwangi Regency to detect early signs of mental disorders and improve adolescent mental health through fun games. The program was conducted on October 6, 2023, at SMAN 1 Glagah Banyuwangi with 45 participants. The training included mental health identification using instruments adapted from the Mental Health Inventory (MHI) and group dynamics activities from Psychodynamic Play Therapy (PPT). Participant satisfaction surveys showed that 100% were very satisfied with the training, with an average rating above 4.6 on a scale of 1-5. Participants indicated that the training positively impacted their understanding of student mental health and the benefits for PJOK teaching. Post-training, 100% of participants rated the delivery method as excellent. The study concluded that the community service activity successfully enhanced PJOK teachers' understanding of adolescent mental health and underscored the importance of early detection and fun games as therapeutic tools. Future activities should involve teachers from all subjects to maximize mental health awareness and adapt to the dynamic conditions of students' mental health